Plant Phenology And Itsrelation TO The Cool Semi-Arid Conditions OF Sana’a - Abulfatih, H. A.; Al-Ani, M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In the cool semi-arid highland areas of Sana’a, a plant phonological study of forty two species revealed that there was one major outburst of plant emergence corresponding with the first period of the heavy rainfall which take place during March-April. The second period of heavy rainfall which takes place during July-August shows moderate effect on emergence and growth. Plant Species included annuals, biennials and perennials. Perennials showed the following growth forms hemicryptophytes, chamaephytes, phanerophytes, and cryptophytes. Most plants where herbaceous and a few where woody Different Individuals of the same species could behave as annuals, biennials or perennials. In areas where soil moisture lasted for a short period, plants behaved annuals, and in areas where moisture lasted for longer periods, the plants behaved as biennials or perennials. The prolonged period of leafing, flowering and fruiting experience by most species also was caused by the moderate temperature which prevailed during the year Leafing, flowering and fruiting periods varied among species. However, they prevailed from March to November. Growth of most